The relationship between two types of impaired emotion processing: repressive coping and alexithymia - Myers, Lynn B.; Derakshan, Nazanin (Frontiers in Psychology, 2015)
The constructs of repressive coping and alexithymia are both related to impaired emotion processing, yet individuals with a repressive coping style (repressors) score lower than controls on standard self-report measures of alexithymia. A large body of evidence indicates that repressors avoid negative affect. Therefore, the current study examined the relationship between repressive coping and alexithymia by using independently-rated interviews with the aim of bypassing repressors’ tendency of avoiding negative affect. Results showed that repressors scored high on alexithymia, similar to anxious individuals on the independently-rated interview, but scored low on alexithymia on a questionnaire measure. Our findings confirm a link between alexithymia and repressive coping and stress the need for nonstandard measures in exploring the nature of the relationship between repressive coping and alexithymia.